The Effectiveness of Online Education Through Digital Posters on Increasing Pregnant Women's Knowledge About Childbirth Preparation - Fitria Fitria; Ummul Fadhilah; Sri Muliani (Jurnal EduHealth, 2025)
The low level of understanding among some pregnant women regarding childbirth preparation remains a challenge in efforts to improve maternal and neonatal preparedness and safety. This study aims to analyze the effectiveness of online education delivered through digital posters in improving pregnant women’s knowledge of childbirth preparation in Makassar City. The research employed a quasi-experimental design using a one-group pretest–posttest model, involving 30 pregnant women selected through purposive sampling. The educational intervention consisted of sending digital posters containing childbirth preparation materials via the WhatsApp platform, followed by measurements of participants’ knowledge before and after the intervention using a Google Form questionnaire. The results showed a substantial increase in knowledge after the intervention, with the mean score rising from 62.3 in the pre-test to 82.7 in the post-test. Furthermore, the paired t-test yielded a p-value of 0.000 (p < 0.05), indicating that the digital poster–based education had a significant effect on improving pregnant women’s knowledge of childbirth preparation. These findings confirm that digital posters serve as an effective, accessible, and contextually relevant educational medium for pregnant women in urban settings such as Makassar City. The study recommends developing more interactive digital content and conducting further research with control groups and additional variables to strengthen the empirical evidence.